Social Responsibility on Islamic Spiritual Entrepreneurs for Blessing of Life and Successful Entrepreneurship - Janah, Septa Miftakul; Subiyantoro, Subiyantoro (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
The entrepreneurial dimension is not low, it is even a strong attraction in the world of work and good character must always be built for everyone who wants to be successful in life. The concept that should be owned by Muslim entrepreneurs is called Islamic spiritual entrepreneurs, and the concept must be realized with life attitudes, one of which is social responsibility. This paper aims to examine the terminology of Islamic spiritual entrepreneurs and social responsibility through a literature approach. Social responsibility as a manifestation of the spiritual attitude of entrepreneurs offered in this paper can be the key to a person's success in entrepreneurship and achieving blessings in his life. Through this attitude, the entrepreneur's personal branding and personal reputation can be realized so that he will become a money magnet because of the strong trust he has.